The factors of continuous improvement towards customer satisfaction in Urban Transformation Centre (UTC) Melaka / Fatin Izzati Mazilan and Syazana Hazwani Azman - Mazilan, Fatin Izzati; Azman, Syazana Hazwani (Faculty of Administrative Science and Policy Studies, 2013)
The purpose of this study is to investigate The Factors of Continuous Improvement towards Customer Satisfaction in Urban Transformation Centre (UTC) Melaka. The objectives of this study are to identify the most influential factor of continuous improvement which leads to customer satisfaction. The second objective is to determine the relationship between the factors of continuous improvement and customer satisfaction and the last objective in this research is to examine the challenges of continuous improvement programs in the UTC Melaka. In this research, we used convenient sampling technique to distribute the questionnaire. The finding of this research, most influential factor of continuous improvement which leads to customer satisfaction is training and learning of the employee. The result of the second objective is all of the five independent variables which consist of management commitment, teamwork, communication, training and learning and employee empowerment are moderately related with customer satisfaction as our dependent variable. For the conclusion, the management commitment, teamwork, communication, training and learning and employee empowerment are not strongly related with the satisfaction of UTC’S customers.